Adolescent flourishing in relation to having asthma: Results from a population-based cross-sectional study. (1st February 2018) - Nabors, Laura; Odar-Stough, Cathleen; Peugh, James; Merianos, Ashley L.; Cunningham, Jodi; Yockey, Robert Andrew
ABSTRACT: Objective : This study investigated parent report of adolescent behaviors and flourishing of adolescents with asthma from a nationwide sample. Methods : A secondary analysis of the 2011–2012 National Survey of Children's Health was conducted. There were 2, 880 youth with asthma in our sample and 25, 841 without asthma between 13 and 17 years of age. Analyses examined flourishing among adolescents with and without asthma and the impact of adolescent arguing, bullying, and mood difficulties on adolescent flourishing for adolescents with asthma, while controlling for sex, age, and race. Results : Findings indicated lower flourishing for youth with asthma compared to youth without asthma. Moreover, adolescents with asthma who experienced negative behaviors, such as arguing and bullying, and adolescents who were experiencing sad feelings had lower flourishing. Conclusions : The results were consistent with literature, indicating that relatively poorer behavioral and emotional functioning is related to lower flourishing in adolescents with asthma. The results highlight the importance of screening for emotional functioning in adolescents and the need for further research to understand characteristics of adolescents related to their positive functioning.